2008
DOI: 10.1109/tpwrd.2008.919041
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Probabilistic Design Procedure for LV Residential Distribution Systems

Abstract: Two basic types of low voltage (LV) distribution exist in practice. The systems based on the European approach have long LV feeders whose sizing requires more careful design consideration than systems based on North American practice with shorter LV feeders. The most important criterion in conductor sizing is the correct estimation of the design loads. This paper describes the development and application of a probabilistic design method based on the Beta probability density function (pdf). The paper investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…Table 1 lists voltage exponents for static load models. The voltage exponents of load classes differ from each other because of aggregated load patterns [4][5][6][7][8][9][10].…”
Section: Load Combinationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 lists voltage exponents for static load models. The voltage exponents of load classes differ from each other because of aggregated load patterns [4][5][6][7][8][9][10].…”
Section: Load Combinationsmentioning
confidence: 99%
“…In this scenario, multi-objective approach of reconfiguration provides more flexibility to the utility to operate the system to actively participate in a competitive deregulated environment. Loads, in distribution systems, are modelled as composite loads for power flow and stability studies in [4][5][6][7][8][9][10]. The effect of these load models on EEDPs, that is, active and reactive load demands [5,6], loadability limit [7] and the load demand at the substation with distribution resource placement [11,12], are studied and it was observed that these EEDPs respond differently to these loads.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Load parameters can be estimates from the group after diversity maximum demand (ADMD) for the customers in countries where a large load database is not available, and but this study uses available load data in South Africa. Using the mean and standard deviation of the outage duration distribution, the α and β parameters are calculated as shown in equations 1 and 2 [13]. A typical interruption duration distribution is shown in Figure 6.…”
Section: Probabilistic Model (Case 3)mentioning
confidence: 99%
“…Where µ is mean of the outage duration, σ is the standard deviation and C is the limiting factor [13]. The beta PDF model is used for this study for the following reasons [13]:…”
Section: Probabilistic Model (Case 3)mentioning
confidence: 99%